The role of defects and characterisation of tensile behaviour of EBM Additive manufactured Ti-6Al-4V: An experimental study at elevated temperature. (February 2021) - Gupta, Alok; Bennett, Chris J.; Sun, Wei
Highlights: The poor surface finish and internal defects reduce mechanical strengths at high temperature. For machined specimens, mechanical strengths decrease but ductility increases with temperature. Microstructure and orientation of voids cause anisotropy in mechanical strength response. For vertical built specimens, the lack of fusion voids in-between the layers cause lower ductility. Abstract: The use of the Electron Beam Melting (EBM) Additive Manufacturing (AM) process to fabricate parts for applications which require strength and reliability is limited. EBM parts suffer from manufacturing defects and poor surface finish, and its strength properties can be dependent on strain rates and temperature. In this paper, the effects of parameters such as the strain rate, temperature, surface finish and build orientation together with the role of defects on tensile properties of EBM Ti-6Al-4V alloy have been studied and discussed. Due to reduced material density and multiplication rate of dislocations, a significant decrease in material tensile strength but an increase in material ductility was observed for tests on machined specimens at higher temperatures. Surface nucleating micro-cracks (poor surface finish) and inherent internal defects caused a reduction in tensile strength and material ductility for the as-built specimens. Coalescence of small size spherical pores and the presence of large voids have a direct deleterious effect on the ductility of Ti-6Al-4V alloy. The orientations of voids, difference in thermal history resulting into different microstructures, presence of grain boundary α and alignment of prior columnar β grains with respect to the loading direction for vertical and horizontal built specimens are the reasons for observed anisotropy in material strength of EBM Ti-6Al-4V alloy. The interaction effects of different parameters are also discussed, and it is suggested that these parameters should be optimised, in addition to the process parameters, to make AM parts using the EBM process which can reliably and safely be used for load bearing applications.